Factors predicting the guideline compliant supply (or non-supply) of non-prescription medicines in the community pharmacy setting. Issue 1 (2nd February 2006) - Watson, M C; Bond, C M; Grimshaw, J; Johnston, M
Abstract : Background: The reclassification of prescription only medicines to pharmacy and general sales list medicines (also known as non-prescription medicines) provides the public with greater access to medicines that they can purchase for self-care. There is evidence that non-prescription medicines may be associated with inappropriate supply. This study investigated factors predicting evidence-based (guideline compliant) supply or non-supply of non-prescription medicines. Method: Secondary analysis of results from a randomised controlled trial of educational interventions to promote the evidence based supply of non-prescription medicines. Ten actors made simulated patient (customer) visits to 60 community pharmacies using seven scenarios reflecting different types of presentations. The dependent variable was appropriate (guideline compliant) supply of antifungal medication for treatment of vaginal candidiasis. Results: No significant association was shown between guideline compliant behaviour and pharmacy type or location, or with the actor making the visit. The likelihood of guideline compliant outcome was significantly greater with symptom presentations than with condition or product presentations (p<0.001). The likelihood of a guideline compliant outcome increased (a) as more information was exchanged (p<0.001), (b) with the use of WWHAM (a mnemonic frequently used by medicine counter assistants during consultations for non-prescription medicines) (p<0.001); (c) when specific WWHAM questions were used (including "description of symptoms" (p<0.001) and "whether other medication was currently being used" (p<0.001); and (d) in consultations involving solely pharmacists compared with those involving only medicine counter assistants (p = 0.017). After adjustment for presentation type, a significant association persisted between appropriate outcome and consultations with WWHAM scores of 2 and ⩾3, respectively. Conclusions: The nature and extent of information exchange between pharmacy staff and customers has a strong influence on the guideline compliant supply of non-prescription medicines. Future interventions to promote the safe and effective use of non-prescription medicines should address the apparent deficit in communication between pharmacy staff in general, and medicine counter assistants in particular, which may reflect both pharmacy staff skills and customer expectations.